Sub-20 nm GaAs junctionless FinFET for biosensing application. (February 2019) - Chhabra, Anuj; Kumar, Ajay; Chaujar, Rishu
Abstract: This work proposes a dielectric modulated GaAs junctionless FinFET as a biological sensor in the sub-20 regime. In the proposed biosensor, HfO2 (ᴋ = 25) is used as a base oxide which is found to have improved the switching ratio (three times) of the device. For immobilizing the biomolecules, a Nano-cavity (18 nm) is embedded between gate and source/drain. For the detection of biomolecules, electrical characteristics such as switching ratio, energy band profile and change in surface potential have been studied and thereafter, sensitivity has been evaluated which has been improved by 80%. Change in current is recorded for different materials due to change in gate capacitance owing to different biomolecules: Protein (ᴋ = 8), streptavidin (ᴋ = 2.1), biotin (ᴋ = 2.63). Higher sensitivity is observed for protein biomolecules (1.07) as compared to streptavidin (1.015) and biotin (1.045). The sensitivity is compared to with the absence of biomolecules (assumed as the vacuum) as well. Furthermore, modulation of the cavity gap length was also investigated, revealing that its increase (from 8 to 18 nm) significantly enhanced the sensitivity of the proposed biosensor. All the results pave way for biomolecule detection with the existing CMOS technology. Highlights: GaAs Junctionless FinFET as a highly sensitive protein biosensor is proposed. The device is more sensitivity for protein biomolecules as compared to streptavidin and biotin. The results are compared with the presence of biomolecule and vacuum (absence of biomolecule). The impact of nano cavity gap length variation has also been examined. This device is useful for early diagnosis of deadly diseases to improve the health.